2022
DOI: 10.3390/polym14224910
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Diffusion Coefficient of Polyimide Film for Capacitive Humidity Sensors

Abstract: Polyimide (PI) film is widely used as the key component of the capacitive humidity sensor, whose diffusion coefficient has a significant impact on the sensor’s dynamic characteristics, but is rarely discussed. This paper provides a test method and processes for effective diffusion coefficients of water molecules in self-synthesis PI films. The films were formed by four ingredients (PMDA-ODA, BPDA-ODA and BPDA-BAPP, PMDA-BAPP) with PI acid concentrations of 23%, 20%, 17% and 15%, and tested in temperatures of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The water absorption of the sample increased linearly with time and tended to stabilize after reaching the maximum water absorption. Wu calculated the effective D of PI membranes synthesized from several different monomers, 19 and the results showed that. With the decrease of pores on the membrane, the narrower the diffusion path of water molecules in the membrane, the greater the diffusion resistance.…”
Section: Principlementioning
confidence: 99%
“…The water absorption of the sample increased linearly with time and tended to stabilize after reaching the maximum water absorption. Wu calculated the effective D of PI membranes synthesized from several different monomers, 19 and the results showed that. With the decrease of pores on the membrane, the narrower the diffusion path of water molecules in the membrane, the greater the diffusion resistance.…”
Section: Principlementioning
confidence: 99%